Modeling and Experimental Study of Tin Whiskers for 3D Electronic Packaging - WANG Zekun, ZHANG Fuxi (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
The release of compressive stress and atom diffusion have important influences on the growth of whiskers in 3D electronic packaging, and the compressive stress is also one of the main factors for dynamic recrystallization (DRX). By using the mathematical model of growth mechanism and the behavior of tin whisker based on the finite element method, the process of forming whiskers on silicon substrate by 3D electronic packaging tin layer with a typical physical size and structure was simulated. The qualitative analysis and growth of whiskers were realized. By controlling the key parameters such as gas pressure, thermal cycling temperature, and cycle of Ar in the background of the experiment, the external factors and plating process were constructed. The experimental system of accelerated test of internal pressure stress and whisker growth speed, length, and density in the film was constructed. The growth rate and density of whiskers were observed and detected by SEM. The effectiveness of the mathematical model of stress release, atom diffusion, and DRX in 3D electronic packaging tin whiskers was verified by SEM. The quantitative description of whiskers was realized, providing constructive suggestions for reducing whisker problems in future 3D packaging microstructure graphic design.